1994
DOI: 10.1111/j.1570-7458.1994.tb01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Helicoverpa zea larval behavior by the parasitoid Eucelatoria bryani

Abstract: The parasitoid Eucelatoria bryani Sabrosky regulates the larval behavior of its host Helicoverpa zea (Boddie). Parasitized third, fourth and fifth instars burrow into the soil 0.7-3.4 days earlier than unparasitized larvae that normally enter the soil to pupate at the end of the fifth and final larval instar. Parasitized third instars molt once then burrow as fourth instars, one instar earlier than normal. When E. bryani pupariated on the soil surface in the field, none survived to the adult stage. However, E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In the current study, the experimental set-up did not enable the measurement of resultant parasitoid fitness and, as such, we cannot conclude with certainty if the observed changes to aphid behaviour are beneficial to the parsitoid. However, since there is much research evidence to suggest that manipulation by parasitoids impacts the mobility of the hosts [12, 14, 1922], it is possible that the change in behaviour observed in the current study is also favourable to the parasitoid host and, if shown to enhance parasitoid fitness, may be classified as host manipulation and not simply a pathological by-product.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the current study, the experimental set-up did not enable the measurement of resultant parasitoid fitness and, as such, we cannot conclude with certainty if the observed changes to aphid behaviour are beneficial to the parsitoid. However, since there is much research evidence to suggest that manipulation by parasitoids impacts the mobility of the hosts [12, 14, 1922], it is possible that the change in behaviour observed in the current study is also favourable to the parasitoid host and, if shown to enhance parasitoid fitness, may be classified as host manipulation and not simply a pathological by-product.…”
Section: Discussionmentioning
confidence: 91%
“…Within the context of parasitoid wasps, documented changes to the host following parasitization fall into the category of parasite adaptations, with enhanced parasitoid fitness commonly attributed to behavioural changes induced in the host which bring about a reduction in the rate of predation and hyperparasitism [1214], However, whilst host manipulation by parasitoids is well documented, the potential for host manipulation to enhance thermotolerance is a topic that has received considerably little research attention. There is evidence to suggest that a parasitoid may alter both the physiology and the behaviour of the host to withstand or avoid unfavourable thermal conditions, although both mechanisms have been studied in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, E. spp. Other parasitoids base oviposition decisions on external cues of host condition (Strand & Vinson, 1983;Schmidt & Smith, 1985;McBrien & Mackauer, 1990), and parasitized H. zea do show pathological signs that are correlated with parasitoid development (Reitz & Nettles, 1994). Oviposition, which can be rapid (occurring in less than 2 sec), consists of the female approaching a host, then standing on the dorsum of the host, where the parasitoid may use her forelegs to palpate the host, and finally oviposition (Reitz, unpubl.).…”
Section: Discussionmentioning
confidence: 99%
“…The hosts may only be altered by the activity of the feeding parasitoid larvae. In a very limited number of cases such changes have been found (or hypothesized) to be beneficial to tachinids (Reitz and Nettles 1994;Karban and English-Loeb 1997). Otherwise many tachinids behave as ''conformers'' sensu Lawrence (1986) and show a developmental synchrony with the host.…”
Section: Host-parasitoid Developmental Interactionsmentioning
confidence: 95%
“…In fact, the tachinids that do not depend on host hormones, and form secondary funnels, grow continuously until pupation, but keep the host alive longer than those that build primary funnels (Mellini 1991). One of them, E. bryani, has also been reported to regulate the larval behaviour of its host Helicoverpa zea (Boddie) (Reitz and Nettles 1994). For another one, Compsilura concinnata, Caron et al (2010) have recently shown that the host-parasitoid interactions are widely influenced by host stage at parasitization and larval development is faster in older hosts.…”
Section: Host-parasitoid Developmental Interactionsmentioning
confidence: 98%